ANALYSIS AND MASTER LEARNING MOTOR SKILLS - Siti Hafsoh; Neviyarni (Yayasan Citra Dharma Cindekia, 2021)
Learning can be defined as a mental activity that occurs due to active interactions between individuals and their environment that produce change. Learning is also said to be a process of activity that takes place in a person that changes his behavior both in thinking, behaving, and doing (W.Gulo, 2002: 23). Learning as an activity is actually an individual stimulus to acquire a skill, one of which is motor skills. Motor skills are the ability to learn to result in maximum defined movements. Motor learning is a relatively permanent change in the ability to perform a skill as a result of practice or experience. The goal of motor skills is to optimize the ability to perform these skills at a level of success, accuracy, and to reduce the energy consumption required for performance.